2016
DOI: 10.1039/c5lc01341k
|View full text |Cite
|
Sign up to set email alerts
|

On-chip droplet production regimes using surface acoustic waves

Abstract: Aqueous droplets suspended in an immiscible carrier fluid are a key tool in microfluidic chemical analysis platforms. The approaches for producing droplets in microfluidic devices can be divided into three general categories: batch emulsification, continuous production and tailored on-demand production. The major distinctions between each category are the rate of production and the degree of control over the droplet formation process in terms of the size and quantity. On-demand methods are highly desirable whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 53 publications
(48 reference statements)
0
30
0
Order By: Relevance
“…Fakhfouri et al [10] showed that the acoustic streaming produced by TSAW can make particles swirl and thus form patterns. Brenker et al [23] and Sesen et al [24] proposed droplet generation and droplet fusion methods, respectively, based on TSAW with similar equipment, verifying the effectiveness of TSAW in droplet operations.…”
Section: Manipulation By Sawmentioning
confidence: 94%
See 1 more Smart Citation
“…Fakhfouri et al [10] showed that the acoustic streaming produced by TSAW can make particles swirl and thus form patterns. Brenker et al [23] and Sesen et al [24] proposed droplet generation and droplet fusion methods, respectively, based on TSAW with similar equipment, verifying the effectiveness of TSAW in droplet operations.…”
Section: Manipulation By Sawmentioning
confidence: 94%
“…Similar to magnetic and dielectrophoretic manipulation, VAW uses vibration to excite a wide range of acoustic fields in the medium, where gradient forces are used to manipulate the particles or cells. Acoustic radiation manipulation devices can be used for transport [13][14][15], sorting and filtering [16,17], trapping [18,19], patterning of particles or cells [20][21][22], droplet generation [23], and fusion [24]. Acoustic radiation force can be generated using many methods such as surface acoustic waves (SAWs) and bulk acoustic waves (BAWs).…”
Section: Introductionmentioning
confidence: 99%
“…Acoustouidics has been successfully applied to many different research studies, ranging from micro-droplet production and manipulation to micro-particle (or cell) sorting, focusing, separation, mixing and arraying. [16][17][18][19][20][21][22][23][24][25][26][27] Among these possible applications, cell separation has attracted a lot of attention including substantial effort devoted towards enabling the isolation of circulating tumor cells from human blood samples. [28][29][30][31][32][33][34][35][36] Several groups have demonstrated the possibility of isolating target cells from a given sample containing a mix of cells with different characteristics using acoustouidics.…”
Section: Introductionmentioning
confidence: 99%
“…Some research groups have developed compact, low‐cost, and simple fluid pumping systems for microfluidic droplet generation and there have been a few implementations of such devices. These include piezoelectric (PZT) actuator‐based pumps , responsive hydrogel‐based pumps , degassed poly(dimethylsiloxane) (PDMS)‐powered pumps , and finger squeeze‐driven pumps .…”
mentioning
confidence: 99%